Tales and Novels of J. de La Fontaine $1 (BVolume 22s - La Fontaine, Jean de, 1621-1695 (Salt Lake City, UT : Project Gutenberg, 2004)
"Tales and Novels of J. de La Fontaine $1 (BVolume 22" by Jean de La Fontaine is a collection of tales written during the 17th century, reflecting the literary style of the French classical period. This volume presents a series of fables and stories that explore themes of human behavior, social norms, and morality, often with a humorous twist. La Fontaine's works are known for their insightful commentary on society, using animals and other characters to illustrate various moral lessons. The book features three distinct tales: "The Picture," "The Pack-Saddle," and "The Ear-maker and The Mould-Mender." In "The Picture," two nuns, eager for romantic entertainment, devise a plan that unexpectedly leads to chaotic yet amusing consequences. "The Pack-Saddle" tells a story of a jealous painter whose insecurities about his wife's fidelity lead to absurd situations, showcasing the folly of jealousy. Lastly, "The Ear-maker and The Mould-Mender" explores themes of deception and revenge, where a husband, suspicious of his wife's neighbor, concocts a clever plot for retribution when he learns of the neighbor's advances. Throughout these tales, La Fontaine expertly weaves wit and wisdom, providing both entertainment and moral insight. (This is an automatically generated summary.)s
The Picture -- The Pack-Saddle -- The Ear-maker, and The Mould-Mender.
Release date is 2004-03-01
This eBook was produced by David Widger
Keywords: French poetry -- Translations into English; Fables, French -- Translations into English